Optimization of Samapta Unit Patrol in Preventing Cases of Theft with Violence in the Jurisdiction of the Madiun City Police - Baskara, Arya Krisna (Advances in Police Science Research Journal, 2024)
The focus of this thesis research was motivated by the phenomenon of high cases of theft in Madiun City, especially in this case Theft With Aggravation (Curat). Therefore, a study was conducted to describe the implementation of patrols, and optimization of patrols in the prevention of Curat in Madiun City. To overcome this, the Madiun City Police through the function of the Samapta Unit with patrol activities seeks to reduce Curat crimes in the jurisdiction of the Madiun City Police Station. The theories and concepts used by the author in answering problems are Management theory, situational crime prevention theory, optimization concepts, and Perkabaharkam No. 1 of 2017 concerning Patrol.This research was conducted with a qualitative approach and used the type of field research (field research). The findings of this study, namely in the implementation of patrols, and efforts to optimize patrols of the Samapta Unit were analyzed with Perkabaharkam no. 1 of 2017 concerning patrols and the latest regulations, namely Kepkabaharkam Number: Kep / 403 / V / 2023 concerning Precision Pioneer Patrols Samapta Polri. The results found in the implementation have not been carried out optimally with the findings of the implementation of administrative preparation, the use of sarpras has not been makasimal and at the time of implementation there is no periodic reporting and the patrol results are not made directly after the activity. As well as for patrol optimization by using situational crime prevention theory to create unfavorable situations for criminals Based on the results of the study, the conclusion found that the implementation of patrols has not been optimal in preventing Curat, there are still some obstacles in the implementation of patrols and patrol activities as a means of preventing criminal acts with the creation of situations that do not support the implementation of criminal acts, so the author suggests a proposal to improve the quality and quantity of members and the use of technology to supervise the implementation of patrols.